PENGARUH MODEL PEMBELAJARAN INQUIRY BERBANTUAN MEDIA ANIMASI TERHADAP KOMPETENSI PENGETAHUAN IPA - Ayu Cintya Dewi (Universitas Pendidikan Ganesha, 2018)
This study aimed at determining the significant effect of science knowledge competence between groups of students who are taught by using inquary learning model which assisted by animated media with groups of students who are taught through conventional learning in fourth grade students of SD Gugus Dewi Sartika academic year 2017/2018. This study was a quasi experimental research with non-equivalent control group design. The population of this study was all fourth grade students of SD Gugus Dewi Sartika which amounted to 266 students. The sample was determined by random sampling technique so that there would be fourth grade of SD Negeri 3 Pedungan as experiment group which amounted to 45 people and fouth grade B of SD Negeri 13 Pedungan as control group which amounted to 30 people. The data collection in this research was done by the test method and the instrument used in the form of ordinary double choice objective test. Data of knowledge competence was analyzed by t-test polled variance. The analysis result indicated that there was a significant effect of science knowledge competence between group of students which was taught by using inquary learning model which assisted by animated media with group of students that was taught by using conventional learning in fourth grade students of SD Gugus Dewi Sartika academic year 2017/2018. Thus, it can be concluded that Inquiry Learning Model which assisted by animated media have a significant effect on science knowledge competence of fourth grade students of SD Gugus Dewi Sartika academic year 2017/2018, and the Inquiry Learning Model which assisted by animated media can be used in studying science so as to create the kind of learning. Keywords : Inquiry, Animation , Science Knowledge Competence